1989
DOI: 10.1080/00306525.1989.9633753
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Responses of Birds to Fire in Old Mountain Fynbos

Abstract: FRASER, M. W. 1989. Short-term responses of birds to fire in old Mountain Fynbos. Ostrich: 60: 172-182. Observations of birds were made from six weeks before until one year after a fire in 28-year-old Mountain Fynbos vegetation near Stellenbosch, Cape Province, South Africa. No fire attendance by birds was observed, in contrast to observations made at fires in other southern African vegetation types. Bird species composition in the study site as a whole was virtually unchanged after the fire. With the excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Together, these results suggest that nectar-feeding birds show a strong preference towards unburnt habitat. This result complements the observation by Fraser and McMahon (1992) and Fraser (1989) who found that the abundance of nectarivorous birds declined more than any other feeding guild after a fire in fynbos vegetation. Our study builds on these findings by showing that flower visitation declines in unison.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Together, these results suggest that nectar-feeding birds show a strong preference towards unburnt habitat. This result complements the observation by Fraser and McMahon (1992) and Fraser (1989) who found that the abundance of nectarivorous birds declined more than any other feeding guild after a fire in fynbos vegetation. Our study builds on these findings by showing that flower visitation declines in unison.…”
Section: Discussionsupporting
confidence: 92%
“…sunbirds (Nectarinidae) and sugarbirds (Promeropidae), suffer greater declines than other bird guilds after fires (Fraser 1989;Fraser and McMahon 1992). Taken together, these observations suggest that bird-pollinated plants flowering in a post-fire landscape might suffer severe pollinator limitation (Fraser 1989;De Swardt 1993;Pauw 2004).…”
Section: Introductionmentioning
confidence: 98%
“…The structure of the Berzelia intermedia -Erica melanthera shrubland differs from that (McDonald 1993). The Cape Sugarbird, for example, is associated with tall, mature proteas, which are absen t from the Berzelia intermedia -Erica melanthera community (Fraser 1989;McDonald 1993).…”
Section: Discussionmentioning
confidence: 95%
“…The findings ofArmstrong and van Hensbergen (1994) for the bird assemblages of mature pine plantations at ]onkershoek, southwestern Cape, were similar. The common species recorded on the fyn bos plot and forest plot at Grootvadersbosch are characteristic of tall sparse shrubland and tall forest/ closed woodland, respectively, at]onkershoek (Fraser, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…It has been the focus of one study, which primarily documented the distribution and diet of the species (Milewski 1976(Milewski , 1978. Apart from one other note on aspects of its occurrence (Fraser & Richardson 1989), and a small amount of capture-recapture work that concluded the species was robust to a controlled fire event (Fraser 1989), little is known about the basic biology of the species. Most recently, modelling exercises based on atlas data on the impacts of climate change have predicted range-contractions for this species in a drier and warmer future climate (Huntley & Barnard 2012).…”
mentioning
confidence: 99%